Profile of Collaboration Skills in Learning Renewable Energy Materials - Djano, Umi Kalsum; Saepuzaman, Duden; Samsudin, Achmad; Aviyanti, Lina; Muslim, Muslim; Fitriani, Fitriani (PAEDAGOGIA, 2025)
This study aims to determine students’ collaborative skills in renewable energy learning, an essential skill in 21st-century education. This study employs a descriptive approach using qualitative methods to detail the level of students’ collaborative skills. Data was collected using a Likert-scale collaborative skills questionnaire. The research subjects consisted of 30 high school students, and data was analyzed using the average percentage scores for each collaborative skill indicator. The results indicate that most students possess relatively high collaborative skills, with the majority scoring above 70%. The average score on the collaboration indicators was 80.33%, with Indicator 1 scoring 81, Indicator 2 scoring 78, and Indicator 3 scoring 82. The respondent with the highest collaboration score was R13, with a score of 97%, while the respondent with the lowest collaboration score was R17, with a score of 25%. The significant variation in scores, ranging from 25% to 97%, indicates substantial differences in student collaboration skills. Factors influencing these skills include ineffective communication, poorly managed differences of opinion, and low empathy toward group members’ contributions. The implications of this study emphasize the need for collaboration-enhancing strategies, such as interpersonal communication training, conflict management, and empathy development within groups. These strategies should be explicitly integrated into project-based learning designs, particularly regarding renewable energy, to enhance students’ overall collaboration effectiveness.